Burning man : learning from Heterotopia - Noveroske, Linda (London ; New York : Routledge, 2024)
"This book centres on a philosophical analysis of creative acts in the Burning Man Festival and their roles in wider social change. With particular focus on the Ten Principles of Burning Man, Linda Noveroske posits a re-interpretation of common notions of "self" and "other" as they apply to identity, difference, and the ways that these personal impulses ripple outward from changing individuals into changing societies. Such radical re-imagination of ideology can be most powerful when it occurs in spaces of otherness, of heterotopia. This study casts Burning Man as a heterotopia to not only destabilizes what we think we know about visual art, performance, and creative encounters, but also bring these acts into an attitude of immediacy that facilitates previously unimagined behaviour and opens out artistic drive into the unknown. This book would be of value for scholars and practitioners in Performance Studies, Theatre and Dance, Art History, Psychology, Phenomenology, Architecture and Urban Studies"--
Keywords: Performance art; Counterculture; ART / History / General; PERFORMING ARTS / Theater / General; PERFORMING ARTS / Theater / History & Criticism